PENGGUNAAN BERBAGAI JENIS BOKASHI LIMBAH PASAR TERHADAP PERTUMBUHAN DAN HASIL TANAMAN OKRA (Abelmoschus esculentus) PADA TANAH GAMBUT (Utilization of Traditional Market Waste on The Growth and Yield of Okra (Abelmoschus esculentus) Grown in Peat Soil) - B., Aswara,; rudin, Syah; H.E.N.C., Chotimah, (AGRIPEAT, 2017)
ABSTRACTThe purpose of this research was to know the best market waste that can increase the nutrient on peat soil, and to know the best kind of raw material of organic fertilizer that can give the best growth and yield of okra in peatsoil. The experiment design conducted Completely Randomized Design with single factor consisting seven levels of dosage bokashi namely without bokashi, fish waste bokashi 20 t ha-1, fish waste bokashi 30 t ha-1, vegetables waste 20 t ha-1, vegetables waste 30 t ha-1, fruit waste 20 t ha-1, and fruit waste 30 t ha-1. The results showed that provision of fish waste 30 t ha-1 could increase plant height (33.4 cm), number of leaf (34) and yield of okra (688 g) at 5 week after planting (WAP).Key words : Okra, market waste, bokashi, peat soil